A peridynamic elasto-plastic damage model for ion-irradiated materials. (1st January 2023) - Nowak, M.; Mulewska, K.; Azarov, A.; Kurpaska, Ł.; Ustrzycka, A.
Abstract: This study presents the novel peridynamic constitutive relations formulated in order to predict the plastic deformation and damage evolution in irradiated materials. The plastic behaviour of the material in which radiation induced defects contribute to the defined peridynamic porosity is described by the Gurson–Tvergaard–Needleman (GTN) yield criterion with irradiation hardening. The definition of peridynamic porosity is proposed as a volume of discontinuities created in the volume of peridynamic particles. The new constitutive relations for irradiation hardening based on the dilatational part of elastic strain energy are formulated. The physical relevance of coupling the porosity with the nonlinear irradiation hardening is discussed. The expressions for the yield function, kinetics of evolution of radiation induced porosity, irradiation hardening and plastic flow rule are derived in terms of the peridynamics variables. The peridynamic predictions are calibrated based on the experimental data obtained during the advanced experimental campaigns dedicated to irradiated materials to verify the validity of the proposed constitutive model. Ion irradiation campaigns were carried out to mimic the effects of neutron irradiation. A series of indentation experiments were conducted to elucidate the effects of material structure modification and assess the hardening effect originating from radiation defects. Graphical abstract: Highlights: New peridynamic constitutive model is formulated for irradiated materials Nonlinear relations of the irradiation hardening are introduced Radiation induced porosity is defined at the level of the peridynamic particle The plastic behaviour of the material is described by the GTN yield function Irradiation campaign using a tandem accelerator has been carried out